Between Regulation and Reality: Reflections on State Responsibility and the Effectiveness of Criminal Law in Dealing with Cybercrime in Indonesia - Risal, M. Chaerul; M. Majdy Amiruddin; Muh. Ikram Nur Fuady (Al-Risalah, 2025)
The development of information technology has brought about complex legal consequences, particularly in the field of cyber criminal law. The case of personal data leaks by a hacker known as Bjorka in 2022, the ransomware attack on Bank Syariah Indonesia (BSI) in 2023, and the leak at the National Data Centre in 2024 highlight the weakness of cyber security systems and the state's suboptimal responsibility in protecting personal data. This study aims to analyse the effectiveness of Indonesian criminal law in combating cybercrime and the state's responsibility in ensuring digital security for the community. Using a normative legal research method, data was obtained through a review of legislation, literature, and actual cases. The results of the study show that Indonesian criminal law, particularly through Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law) as amended by Law No. 19 of 2016, as well as Law No. 27 of 2022 concerning Personal Data Protection, has not been able to provide an adequate deterrent effect due to weak law enforcement, limited cyber resources, and the absence of a clear state accountability mechanism in cases of public data leaks. Therefore, it is necessary to reconstruct criminal law policies and strengthen digital forensic capabilities so that the protection of personal data in cyberspace can be effectively guaranteed.